2006
DOI: 10.1007/s10722-004-1931-8
|View full text |Cite
|
Sign up to set email alerts
|

ISSR Variation in Olive-tree Cultivars from Morocco and other Western Countries of the Mediterranean Basin

Abstract: In olive tree (Olea europaea L.), 12 varieties (or cultivars) representing the main domesticated material used in Morocco and 19 olive cultivars used extensively in five countries of the western Mediterranean Basin, were analysed using inter-simple sequences repeat (ISSR) markers which had never been used previously for extensive discrimination of cultivars. Four selected primers produced a total of 26 polymorphic reproducible amplification fragments. Combinations of these ISSR markers allowed to identify 25 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
2
28
0
3
Order By: Relevance
“…The high level of polymorphism at ISSR loci also indicates high genetic variability in wild olive trees, which is in agreement with other studies made on cultivated (Gemas et al, 2004;Terzopoulos et al, 2005;Essadki et al, 2006;Gomes et al, 2009;Martins-Lopes et al, 2009) and wild olive trees (Hess et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The high level of polymorphism at ISSR loci also indicates high genetic variability in wild olive trees, which is in agreement with other studies made on cultivated (Gemas et al, 2004;Terzopoulos et al, 2005;Essadki et al, 2006;Gomes et al, 2009;Martins-Lopes et al, 2009) and wild olive trees (Hess et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the genetic diversity was found to be attributable to differences among genotypes within a country. Belaj et al (2002), Terzopoulos et al (2005) and Essadki et al (2006) observed various groupings of Greek cultivars based on ISSR markers. Omrani-Sabbaghi et al (2007) did not find any particular clustering between seven Greek genotypes using SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular studies have discriminated various Greek olive cultivars (Fabbri et al, 1995;Besnard et al, 2000Besnard et al, , 2001aBelaj et al, 2001Belaj et al, , 2002Nikoloudakis et al, 2003;Rallo et al, 2003;Owen et al, 2005;Terzopoulos et al, 2005;Hagidimitriou et al, 2005;Montemurro et al, 2005;Díaz et al 2006b;Essadki et al, 2006;Omrani-Sabbaghi et al, 2007;Bracci et al, 2009). Greek genotypes seem to carry the same chloroplast DNA polymorphisms (Besnard et al, 2000) and the same mitotypes (ME1), except Amigdalolia, which carries the ME2 mitotype (Besnard et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…In other woody species, AFLP and ISSR have also been used in analysis of genetic diversity in Citrus spp. (Fang and Roose 1997;Biswas et al 2011), Vitis vinifera L. (Moreno et al 1998;Ergül et al 2006) or Olea europea L. (Essadki et al 2006;Albertini et al 2011). In Portugal, the number of landraces has decreased in the last decades and the few ones actually identified have been poorly characterized.…”
Section: Introductionmentioning
confidence: 99%